GCSDB: an integrated database system for the Georgia Centenarian Study - Dai, Jianliang (Biomedical Informatics Publishing Group, 2006)
GCSDB is a web-oriented integrated database system for the Georgia Centenarian Study, a phase III, population-based, multidisciplinary study of centenarians. The Study recruited 244 centenarians and near-centenarians (age 98 and older), 80 octogenarians and 400 young controls in Northern Georgia. GCSDB incorporates more than 40 relational tables containing data about the participants including demographics, family longevity, physical health, cognition, neuropsychology, mental health, neuropathology, functional capacity, and genetics. The GCSDB web site includes detailed information about these tables and functions for genetic and other kinds of data analysis. More data and functions will be added as the study progresses. GCSDB provides a resource that could be used to identify what biological, psychological, and social factors as well as their epistatic interactions help these centenarians achieve long life. AVAILABILITY: http://qa.genetics.uga.edu (login information can be obtained from authors)